Digital Transformation in the Start-up World: Bibliometrics on Research Trends (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Digital transformation has become a major factor in accelerating growth and innovation in startups. This study aims to provide an overview of the evolution of digital transformation studies in startups globally, as well as propose future research directions to strengthen studies related to digital transformation in resilient startups. The method used was a systematic literature review with a bibliometric analysis and content analysis approach. The research protocol involved 29 articles collected from the Scopus database through a search using Publish or Perish, with the help of Excel and Mendeley for quantitative analysis of the sample and bibliographic management. Bibliometric analysis was conducted using Biblioshiny R Studio and VOSviewer software. Research on digital transformation (DT) in Start-up increased significantly from 2017 to 2024, with the highest number of publications reached in 2023. Through bibliometric analysis and science mapping, four main focuses of research were found, namely innovation, digital business models, digital technology, and digital transformation. In addition, the research also identified five key future trends in DT studies on startups, namely digital business innovation, sustainability, technology adoption, social innovation, and digital entrepreneurship.